2021
DOI: 10.1371/journal.pone.0255160
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of probiotic adjuvant therapy for irritable bowel syndrome in children: A systematic review and meta-analysis

Abstract: Objective Irritable bowel syndrome (IBS) affects children’s quality of life and learning. The purpose of this research was to systematically evaluate the efficacy of probiotic adjuvant therapy for IBS in children. Methods The Web of Science, PubMed, Cochrane Library, EMBASE and Clinical Trials databases were electronically searched for randomized controlled trials (RCTs) published prior to January 2021 exploring the use of probiotic adjuvant therapy for IBS in children. Strict screening and quality evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…On the other hand, symbiotic bacteria establish a mutually beneficial relationship with the host. Some probiotics may become adjuvant therapies in the treatment of certain diseases ( Zhu and Liu, 2017 ; Atefi et al, 2021 ; Xu et al, 2021 ). Therefore, typing pathogenic and probiotic bacteria at the strain level is a tremendous challenge relevant to human health.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, symbiotic bacteria establish a mutually beneficial relationship with the host. Some probiotics may become adjuvant therapies in the treatment of certain diseases ( Zhu and Liu, 2017 ; Atefi et al, 2021 ; Xu et al, 2021 ). Therefore, typing pathogenic and probiotic bacteria at the strain level is a tremendous challenge relevant to human health.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have confirmed the efficacy of different probiotics in improving functional symptoms and QoL in patients with IBS. [26][27][28][29] These studies have also shown improvement in depression and anxiety among patients with IBS. 30 However, there are contradicting results for the optimal dose and duration of probiotic treatment.…”
Section: Discussionmentioning
confidence: 87%
“…In a meta-analysis of 20 IBS randomized clinical trials (RCTs), probiotics improved global IBS symptoms versus placebo (pooled relative risk 0.77, 95% CI 0.62–0.94) [ 41 ]. Probiotics significantly reduced abdominal pain (mean difference −1.15, 95% CI −2.05 to −0.24) in an analysis of nine RCTs in children with IBS [ 40 ]. Thus, gut microbiota remain as a good IBS therapeutic target [ 1 , 10 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Response rate at Week 4 was assessed by GAQ. Proportion of treatment responders at Weeks 4 and 8 was evaluated by the Subject’s Global Assessment of Relief for Children with IBS (SGARC) [ 38 40 ]; treatment response was defined as 0 = complete relief or 1 = considerable relief. At Weeks 4, 8, and 16, records were made in patient diaries for number of stools by day; consistency of stools (Bristol Stool Form Scale); abdominal distention/bloating (3-point scale); number of abdominal pain episodes by day; pain intensity (Face Pain Scale–Revised); and IBS behavior (Behavior Scale).…”
Section: Methodsmentioning
confidence: 99%